Online Learning Motivation of Elementary School Teacher Education Students on The Understanding of Javanese Paramasastra of Perangan Awak Concept - Urip Umayah (Universitas Pendidikan Indonesia Kampus Serang, 2022)
This study aimed to explain in detail how the objective conditions of motivation experienced by students in online learning of Javanese Paramasastra (grammar) of Perangan Awak (part of the body) concept. It is based on the factual conditions of the COVID-19 pandemic, which poses serious problems for face-to-face learning activities in universities. Therefore, online learning motivation is a skill that students must master. This study applied a quantitative approach with a survey method. The research was conducted at University of Nahdlatul Ulama Al Ghazali (UNUGHA), involving 97 4th-semester students in the elementary school teacher education study program. The data collection technique in this study used a survey technique with a Likert scale. The survey was made in a Google form for easy access by students. The data analysis technique employed in this study was to calculate the percentage of data from each indicator, interpret the data presentation scores, and analyze each indicator in depth. This study’s results revealed that the learning motivation of 4th-semester students in the elementary school teacher education program at Nahdlatul Ulama Al Ghazali University was very good, as seen from the percentage of motivation scores, which was 84.07%. Also, efforts to teach the Javanese language to increase students' motivation are to become cool teachers and direct students to practice Javanese Paramasastra of Perangan Awak concept in song covers.